Roles of Interpretation in Wolfgang Iser’s Theory of Reading and Systematic Poetics (ENTHYMEMA, 2017)
On first glance, Wolfgang Iser seems to share little ground with pioneers of poetics like Tzvetan Todorov and Benjamin Harshav, who explicitly excluded interpretation from the province of poetics. Indeed, if Iser has any connection with poetics, and this article argues that he does, it is via the critical fringes of poetics, where excluding interpretation from systematic study of literature was never seen as an option one could choose. Although poetics versus hermeneutics was one of the major theoretical themes of the late 1970’s, Iser is better understood in the context of critical thought aiming to avoid the strict opposition between the two. Delving in turn into Iser’s theory, his analytical practice, and theory of poetics, this essay points out several points where dialogue between Iser’s work and the endeavor of systematic poetics can be productive.
Keywords: poetics; phenomenology; hermeneutics; metahermeneutics